A finite element model for pre‐stressed or post‐tensioned concrete wind turbine towers. (3rd July 2014) - Kenna, A.; Basu, B.
Abstract: Wind turbine support towers have been traditionally formed of structural steel tubular sections, being fabricated in large sections under factory conditions before being transported to site for erection. Given the trend towards developing turbines with hub heights in excess of 90 m, it is now necessary to develop towers of concrete and other materials that can provide improved dynamic properties and ease transportation difficulties over the structural steel solutions. Concrete towers of this height require pre‐stressing to overcome high vertical stresses induced in bending, which would otherwise lead to cracking in the concrete, with a resulting reduction in the tower's natural frequency. In order to properly understand the behaviour of concrete towers, it is necessary to take account of both material and geometric non‐linearity. Material non‐linearity of concrete is well understood, and geometric non‐linearity arises because of the imposition of an initial stress into the concrete by way of the application of pre‐stress. In this paper, a finite element model is proposed, which will describe the concrete as a continuum of four‐noded, two‐dimensional Reisser–Mindlin shell elements. The pre‐stressing tendons are to be represented by one‐dimensional bar elements, with an imposed pre‐stress. For the numerical examples considered in the paper, tendons are modelled to be post‐tensioned and debonded. The effect of varying the design parameter of magnitude of pre‐stress and the time dependence of pre‐stress force has been investigated using the model described. The impact that concrete compressive strength had on overall tower stiffness was also investigated. Copyright © 2014 John Wiley & Sons, Ltd.